FREKUENSI FUNDAMENTAL TIMBRE KOMPANG GRUP DELIMA DI DELIK BANTAN KABUPATEN BENGKALIS: KAJIAN MUSIK MULTIMEDIA - Benny Andiko; Nursyirwan Nursyirwan; Rosta Minawati (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT The title of this research is “The Timbre Fundamental Frequency of Delima Group’s Kompang in Delik Bantan, Bengkalis District: The Study of Multimedia Music.” Kompang is the toneless percussion instrument. Kompang utilizes space from wood and leather materials as the sound source. The method of sound production namely by hitting the instrument in its membrane part produces the kind of “pang” and “pung” sounds.            This research aims at revealing timbre fundamental frequency by using the music software of PreSonus Studio One 3. The research method used is the approach of Fourier’s analytical theory. Research results are in the form of music study and technology, involving how to produce sound. “Pang” and “pung” sounds were applied in 13 hit motifs played with the interlocking technique by 13 Kompang players. The Kompang organology and 13 players’ expressions became the factor of timbre fundamental frequency range. The frequency range of Kompang’s “pang” and “pung” sounds was obtained from the analysis conducted by using the recording media, the music software of Steinberg Cubase 5 and the music software of PreSonus Studio One 3. Based on analysis conducted by using NUGEN Audio Visualizer, it’s found a frequency that is the buzzing sound of Kompang. The buzzing sound is the character of Kompang with the parameters of organology, expression, and cultural background. Keywords:   Fundamental Frequency, Timbre, Kompang, The Study of Multimedia Music, Delik Bantan Bengkalis.